Functionalization of Graphene Oxide with Porphyrins: Synthetic Routes and Biological Applications. Issue 8 (26th August 2020) - Monteiro, Ana R.; Neves, M. Graça P. M. S.; Trindade, Tito
Abstract: Among the available carbon nanomaterials, graphene oxide (GO) has been widely studied because of the possibility of anchoring different chemical species for a large number of applications, including those requiring water‐compatible systems. This Review summarizes the state‐of‐the‐art of synthetic routes used to functionalize GO, such as those involving multiple covalent and non‐covalent bonds to organic molecules, functionalization with nanoparticles and doping. As a recent development in this field, special focus is given to the formation of nanocomposites comprising GO and porphyrins, and their characterization through spectroscopic techniques (such as UV‐Vis, fluorescence, Raman spectroscopy), among others. The potential of such hybrid systems in targeted biological applications is also discussed, namely for cancer therapies relying on photodynamic and photothermal therapies and for the inhibition of telomerase enzyme. Lastly, some promising alternative materials to GO are presented to overcome current challenges of GO‐based research and to inspire future research directions in this field. Abstract : Let's GO ! Graphene oxide (GO) is of particular interest for multiple bioapplications. This Review highlights different routes used to functionalize GO with porphyrins (namely covalent and non‐covalent strategies) and the tailoring of their physicochemical properties to achieve a synergistic effect in cancer therapies. The functionalization of porphyrins with further two‐dimensional materials is also explored.